2000
DOI: 10.1007/s001980070062
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Bone Loss

Abstract: Bone loss leading to osteoporosis is common after the menopause and in the elderly but uncommon in normal young adults without predisposing factors. The risk factors usually associated with osteoporosis include a family history of osteoporosis or fractures, aging, prior diseases, sedentary lifestyle, low calcium intake, hypogonadism, vitamin D deficiency, smoking, and excessive alcohol consumption. However, the issue of drugs has to be considered in 'normal' individuals who present with osteoporosis or bone lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 159 publications
(210 reference statements)
0
34
0
8
Order By: Relevance
“…Furthermore, the first report on improvement in bone turnover after application of the IL-6 receptor inhibitor tocilizumab has been published (21). On the other hand, methotrexate or cyclosporine may have in part unfavorable effects on bone density and quality indicating divergent effects on juxtaarticulare and systemic bone (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the first report on improvement in bone turnover after application of the IL-6 receptor inhibitor tocilizumab has been published (21). On the other hand, methotrexate or cyclosporine may have in part unfavorable effects on bone density and quality indicating divergent effects on juxtaarticulare and systemic bone (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others have reported that CsA treatment in rats causes a high turnover osteoporosis due to increased bone resorption [3,[12][13][14] This is in agreement with the finding of early bone loss in patients receiving CsA and glucocorticoids after heart transplantation [15]. However, the combination therapy used in transplantation patients makes it difficult to detect specific effects of the different drugs [3,5]. CsA treatment has been found to correlate to a slight osteoclast stimulation, osteblast suppression and decreased bone mineral density in renal transplant patients [1].…”
Section: Discussionmentioning
confidence: 81%
“…In addition, Orcel et al found that CsA stimulated bone formation in rat bone and inhibited bone resorption without affecting PTH or vitamin D [12]. In contrast, others have reported that CsA treatment in rats causes a high turnover osteoporosis due to increased bone resorption [3,[12][13][14] This is in agreement with the finding of early bone loss in patients receiving CsA and glucocorticoids after heart transplantation [15]. However, the combination therapy used in transplantation patients makes it difficult to detect specific effects of the different drugs [3,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os glicocorticóides têm grandes efeitos na homeostasia mineral. Os esteróides podem estimular a secreção de paratormônio (PTH) diretamente (5) (8). No rim há diminuição da reabsorção tubular de cálcio e fosfato.…”
Section: Glicocorticóidesunclassified